Case Study : Hai-O Enterprise Sdn Bhd / Muhammad Nurhazim Azman - Azman, Muhammad Nurhazim (2021)
Hai-O Enterprise Sdn Bhd is a large company in the business world in Malaysia. Hai-O is the parent to 28 other subsidiaries. Among the well-known is Hai-O Marketing which implements multi-level business (MLM). Hai-O Enterprise has been operating in Malaysia since 1976 in the field of traditional Chinese medicine, medicinal wines and health products.In 1996, the company was successfully listed on the Second Board of the Kuala Lumpur Stock Exchange Index and in 2007 it entered the Main Index Board of the Kuala Lumpur Stock Exchange. As of October 2008, Hai-O has successfully produced nearly 200 millionaire entrepreneurs in MLM through Hai-O Marketing. Markets quality products and obtains SuperBrand and ISO 9001 recognition.